Perceived chronic social adversity and cyberbullying perpetration among adolescents: the mediating role of rumination and moderating role of mindfulness - Chen, Rui; Hu, Yang; Shi, Hui-fen; Fang, Yong; Fan, Cui-ying (Frontiers in Psychology, 2024)
The prevalence of cyberbullying has brought about many adverse effects on adolescents' mental health. Although current studies have shown that perceived chronic social adversity (PCSA) is closely related to cyberbullying perpetration among adolescents, the underlying mechanism of the relationship between the two remains relatively unclear. This study investigated the association of PCSA, rumination, mindfulness, and cyberbullying perpetration among adolescents, building upon the general strain theory, the general aggressive model, and the limited resource of self-control theory.Methods: A sample of 477 Chinese high school students (M age =15.84 years, SD age =0.67, 49.69% female) completed the Perceived Chronic Social Adversity Questionnaire, the Ruminative Responses Scale, the Child and Adolescent Mindfulness Measure, and the cyberbullying subscale of the Revised Cyber Bullying Inventory. The current study constructed a moderated mediation model to examine the relationship between PCSA and cyberbullying perpetration among adolescents and assessed the mediating role of rumination and the moderating role of mindfulness.The results revealed a significant positive correlation between PCSA and cyberbullying perpetration. Rumination mediated the relationship between PCSA and cyberbullying perpetration, whereas mindfulness moderated the latter half of the mediation pathway. Specifically, compared to adolescents with higher mindfulness, the association between rumination and cyberbullying perpetration is greater for adolescents with lower mindfulness. The results further deepen our understanding of the mechanisms linking subjective perception of negative life events and cyberbullying perpetration among adolescents from the interaction of multiple factors, thus providing a basis for future interventions to encourage adolescents to properly cope with social adversity and promote positive mental health to reduce the risk of cyberbullying.